Cerium-based polishing material, polishing liquid, method for producing polishing liquid, and method for polishing glass

By increasing the cerium oxide content in the cerium-based abrasive materials and controlling the lanthanum dissolution amount, combined with the lanthanum dissolution inhibitor, the problem of cerium-based abrasive materials causing rough skin and dermatitis is solved, and a high-efficiency and low-irritation grinding effect is achieved.

CN119137235APending Publication Date: 2024-12-13RESONAC CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037546.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-07-10
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing cerium-based abrasive materials are prone to cause rough skin and dermatitis during use, and it is difficult to achieve high smoothness and high efficiency surface grinding.

Method used

The cerium-based abrasive material containing mixed rare earth abrasive material particles is used to increase the oxide conversion content of cerium in the oxide conversion content (TREO) of all rare earth elements to be more than 55.0%, and the dissolution amount of lanthanum is controlled in the abrasive liquid. Abrasive solution with low skin irritation was prepared in combination with lanthanum dissolution inhibitors.

Benefits of technology

It effectively reduces the occurrence of skin roughness and dermatitis, improves the grinding speed and surface smoothness, reduces scratches and defects on the grinding surface, and achieves excellent grinding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005110204970000121
    Figure BDA0005110204970000121
  • Figure BDA0005110204970000122
    Figure BDA0005110204970000122
  • Figure BDA0005110204970000161
    Figure BDA0005110204970000161
Patent Text Reader

Abstract

A cerium-based abrasive material containing mixed rare earth-based abrasive material particles, the mixed rare earth-based abrasive material particles containing lanthanum and cerium, the cerium content in terms of oxide in the total rare earth element content (TREO) being 55.0 mass% or more, and the cerium content in terms of oxide in the total rare earth element content (TREO) being 55.0 mass% or more. The amount of lanthanum dissolved in a mixed solution obtained by loading 10 g of the cerium-based grinding material as a slurry component and 40 g of pure water into a 100 mL polyethylene container, loading 130 g of zirconia beads having a particle size of 1 mm as beads, and pulverizing the cerium-based grinding material using a ball mill stand at a container rotation speed of 210 rpm for 30 minutes is 40 mg / L or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a cerium-based abrasive material, a polishing liquid, a method for producing the polishing liquid, and a glass polishing method used in polishing glass materials such as glass substrates used for liquid crystal panels, hard disks, filters for specific frequency cutoffs, and glass substrates for optical lenses. Background Art

[0002] Glass materials are used in a variety of applications, and surface polishing is sometimes required depending on the application. In particular, glass materials such as glass substrates used for liquid crystal panels, hard disks, filters for specific frequency cutoffs, and glass substrates for optical lenses require high smoothness and high efficiency surface polishing.

[0003] In the surface polishing of glass materials that require such excellent polishing performance, cerium-based abrasives such as those described in Patent Documents 1 and 2 are often used.

[0004] Prior Art Literature

[0005] Patent Literature

[0006] Patent Document 1: International Publication No. 2005 / 042661

[0007] Patent Document 2: International Publication No. 2002 / 031079 Summary of the invention

[0008] As glass abrasives, cerium-based abrasives are generally used, and cerium-based abrasives containing lanthanum are used more frequently. Cerium-based abrasives are generally used in the form of slurry dispersed in water. The slurry is neutral to alkaline, and irritates the skin of the user depending on the user, and there is a problem of observing symptoms such as rough skin and dermatitis. Therefore, there is a demand for cerium-based abrasives with lower skin irritation and excellent operability.

[0009] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a cerium-based abrasive, a polishing liquid, a method for producing the polishing liquid, and a glass polishing method that suppress the occurrence of skin roughness and dermatitis.

[0010] The present invention is based on the following discovery: in a cerium-based abrasive containing mixed rare earth abrasive particles containing lanthanum and cerium, the oxide-converted content of the above-mentioned cerium in the oxide-converted content of all rare earth elements (TREO) is 55.0 mass% or more, and the amount of lanthanum dissolved in a mixed solution containing the above-mentioned cerium-based abrasive and obtained by a prescribed method is 40 mg / L or less, which can reduce skin roughness and dermatitis occurring when attached to the skin.

[0011] That is, the present invention provides the following [1] to

[16] .

[0012] [1] A cerium-based abrasive comprising mixed rare earth abrasive particles, wherein the mixed rare earth abrasive particles contain lanthanum and cerium,

[0013] The cerium oxide content in the total rare earth element oxide content (TREO) is 55.0 mass % or more,

[0014] 10 g of the cerium-based abrasive material and 40 g of pure water were placed in a 100 mL polyethylene container, and 130 g of zirconia beads with a particle size of 1 mm were added as beads. The cerium-based abrasive material was pulverized at a container speed of 210 rpm for 30 minutes using a ball mill stand, and the amount of lanthanum dissolved in the resulting mixed solution was less than 40 mg / L.

[0015] [2] The cerium-based abrasive according to [1] above, further comprising a lanthanum dissolution inhibitor.

[0016] [3] The cerium-based abrasive according to [1] above, which is a two-part type comprising a first part and a second part, wherein the first part contains the mixed rare earth abrasive particles and the second part contains a lanthanum dissolution inhibitor.

[0017] [4] The cerium-based abrasive according to [1] above, comprising 0.1 to 10% by mass of fluorine atoms.

[0018] [5] The cerium-based abrasive according to [1] above, wherein the lanthanum oxide-equivalent content in the TREO is 0.01 to 45.0% by mass.

[0019] [6] The cerium-based abrasive according to [2] or [3] above, wherein the lanthanum dissolution inhibitor is one or more substances selected from alkali metal carbonates, alkali metal phosphates, alkali metal hydroxides, alkali metal sulfates, alkali metal nitrates, alkali metal organic acid salts, alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal hydroxides, alkaline earth metal sulfates, alkaline earth metal nitrates, alkaline earth metal organic acid salts, ammonium carbonates, ammonium phosphates, ammonium hydroxides, ammonium sulfates, ammonium nitrates, and ammonium organic acid salts.

[0020] [7] The cerium-based abrasive according to [6] above, wherein the lanthanum dissolution inhibitor is one or more substances selected from the group consisting of alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal organic acid salts, and alkali metal carbonates.

[0021] [8] The cerium-based abrasive according to [2] or [3] above, wherein the molecular weight of the lanthanum dissolution inhibitor is 300 or less.

[0022] [9] The cerium-based abrasive according to [2] or [3] above, comprising 0.001 to 0.9 parts by mass of the lanthanum dissolution inhibitor per 100 parts by mass of the mixed rare earth abrasive particles.

[0023]

[10] A polishing liquid comprising the cerium-based abrasive described in [1] above and one or more substances selected from water and a water-soluble organic solvent.

[0024]

[11] A method for producing a polishing liquid, which is a method for producing the polishing liquid described in

[10] above, comprising a step (I) of mixing the cerium-based polishing material and one or more substances selected from the group consisting of water and the water-soluble organic solvent to form a slurry.

[0025]

[12] The method for producing a polishing liquid according to

[11] above, wherein the cerium-based abrasive contains the lanthanum dissolution inhibitor.

[0026]

[13] A method for producing a polishing liquid, which is a method for producing the polishing liquid described in

[10] above, comprising a step (II) of mixing the cerium-based polishing material, the lanthanum dissolution inhibitor and one or more substances selected from the group consisting of water and the water-soluble organic solvent to form a slurry.

[0027]

[14] A method for producing a polishing liquid, which is a method for producing the polishing liquid described in

[10] , comprising:

[0028] a step (III) of mixing the cerium-based abrasive with one or more substances selected from the group consisting of water and the water-soluble organic solvent to form a slurry; and

[0029] A step (IV) of adding and mixing the lanthanum dissolution inhibitor to the slurry obtained in the step (III).

[0030]

[15] The method for producing a polishing liquid according to

[14] above, wherein the cerium-based abrasive does not contain the lanthanum dissolution inhibitor.

[0031]

[16] A glass grinding method, comprising grinding using the grinding liquid described in

[10] above.

[0032] According to the present invention, a cerium-based abrasive, a polishing liquid, a method for producing a polishing liquid, and a glass polishing method that suppress the occurrence of skin roughness and dermatitis can be provided. DETAILED DESCRIPTION

[0033] Hereinafter, embodiments of the cerium-based abrasive, polishing liquid, method for producing the polishing liquid, and glass polishing method of the present invention will be described in detail.

[0034] In this specification, the terms "50% particle size in the cumulative particle size distribution based on volume" and "D 50 "" is a particle size at 50% in a volume-based cumulative particle size distribution, obtained from a particle size distribution measured using a laser diffraction-scattering method. Specifically, it is a value measured using a Microtrac particle size distribution meter described in the following Examples.

[0035] [Cerium-based abrasives]

[0036] The cerium-based abrasive material of the present embodiment is a cerium-based abrasive material containing mixed rare earth abrasive material particles, wherein the mixed rare earth abrasive material particles contain lanthanum and cerium, and the converted content of the above-mentioned cerium oxide (CeO2) in the converted content of oxides of all rare earth elements (TREO: the abbreviation of Total Rare Earth Oxides (total amount of rare earth oxides)) (hereinafter referred to as "CeO2 amount / TREO") is 55.0 mass% or more.

[0037] Moreover, by charging 10 g of the cerium-based grinding material and 40 g of pure water into a 100 mL polyethylene container, and charging 130 g of zirconia beads with a particle size of 1 mm as beads, using a ball mill stand, the cerium-based grinding material was pulverized at a container speed of 210 rpm for 30 minutes, and the amount of lanthanum dissolved in the obtained mixed solution was less than 40 mg / L.

[0038] The TREO in the cerium-based abrasive of the present embodiment is derived from mixed rare earth abrasive particles.

[0039] From the viewpoint of increasing the polishing rate, the TREO in the mixed rare earth abrasive particles is preferably 85.0 mass % or more, more preferably 90.0 mass % or more, and further preferably 92.0 mass % or more. From the viewpoint of containing elements other than the elements constituting TREO, further increasing the polishing rate, and suppressing the occurrence of surface defects on the polished surface, the TREO is preferably 99.0 mass % or less, more preferably 98.0 mass % or less, and further preferably 95.0 mass % or less.

[0040] The cerium oxide (CeO2) conversion content (CeO2 amount / TREO) in TREO is 55.0 mass % or more, and from the viewpoint of improving the polishing speed, it is preferably 60.0 mass % or more, more preferably 62.0 mass % or more, and further preferably 64.0 mass % or more. In addition, from the viewpoint of ensuring the content of rare earth elements other than Ce and suppressing the occurrence of surface defects on the polished surface, CeO2 amount / TREO is preferably 90.0 mass % or less, more preferably 80.0 mass % or less, further preferably 75.0 mass % or less, and further preferably 70.0 mass % or less.

[0041] From the viewpoint of suppressing the occurrence of scratches on the polished surface, the above-mentioned lanthanum oxide (La2O3) conversion content in TREO (hereinafter referred to as La2O3 amount / TREO) is preferably 0.01% by mass or more, more preferably 1.0% by mass or more, further preferably 10.0% by mass or more, further preferably 20.0% by mass or more, and further preferably 30.0% by mass or more. Since the Ce amount in TREO is 55.0% by mass or more, the La2O3 amount / TREO is 45.0% by mass or less, and from the viewpoint of increasing the polishing speed and further reducing the rough skin and dermatitis, it is preferably 40.0% by mass or less, more preferably 37.0% by mass or less, and further preferably 35.0% by mass or less.

[0042] It should be noted that TREO can be measured by a gravimetric method through oxalate precipitation and calcination. Specifically, it can be measured by the method described in the examples described later.

[0043] In addition, the content of each rare earth element such as Ce and La can be measured by equipment analysis such as high-frequency inductively coupled plasma (ICP) analysis and fluorescent X-ray analysis. In this embodiment, the value obtained by converting each rare earth element into an oxide is used as the oxide conversion amount based on the measurement value based on ICP emission spectroscopy analysis (ICP-AES).

[0044] The reason why the cerium-based abrasive of the present embodiment can suppress skin roughness and dermatitis is not yet clear, but is considered to be as follows.

[0045] The lanthanum contained in the cerium-based abrasive material is dissolved and dissolved as lanthanum ions in water, water-soluble organic solvents, etc. when the cerium-based abrasive material is manufactured or slurried. If the lanthanum dissolving amount in the liquid is large, it is combined with the chloride ions, etc., of the raw material derived from the cerium-based abrasive material to generate toxic lanthanum chloride, etc., which adheres to the skin of the human body and causes rough skin and dermatitis. On the other hand, it is believed that by making the lanthanum dissolving amount be a low concentration below 40 mg / L, the generation of lanthanum chloride, etc. can be suppressed, and as a result, the generation of surface roughness, dermatitis, etc. can be suppressed.

[0046] The amount of lanthanum dissolved in the mixed solution obtained by the method specified above is 40 mg / L or less, preferably 35 mg / L or less, more preferably 30 mg / L or less, and further preferably 25 mg / L or less from the viewpoint of further suppressing the occurrence of rough skin and dermatitis, and preferably 0.1 mg / L or more, more preferably 0.5 mg / L or more, and further preferably 1.0 mg / L or more from the viewpoint of cost. Furthermore, when the cerium-based abrasive of the present embodiment is used in a slurry state in a real machine, the ratio of the cerium-based abrasive in the slurry to the water and water-soluble organic solvent as the dispersion medium is sometimes different from the case of the method specified above, but if it is below the lanthanum dissolution concentration measured by the determination method, the effect of the present embodiment is apparent.

[0047] In this specification, the "lanthanum dissolution amount" is a value calculated by ICP analysis, specifically, a value calculated by the method described in the following Examples.

[0048] During the production and slurrying of the cerium-based abrasive, chloride ions derived from the raw material of the cerium-based abrasive are dissolved in water, a water-soluble organic solvent, or the like together with lanthanum ions.

[0049] From the viewpoint of further suppressing the occurrence of skin roughness and dermatitis, the amount of chlorine dissolved in the mixed solution obtained by the method specified above is preferably 40 mg / L or less, more preferably 35 mg / L or less, and further preferably 25 mg / L or less. From the viewpoint of cost, it is preferably 0.1 mg / L or more, more preferably 0.5 mg / L or more, and further preferably 1.0 mg / L or more.

[0050] In this specification, the "chlorine dissolution amount" is a value calculated by IC analysis, and specifically, a value calculated by the method described in the following Examples.

[0051] From the viewpoint of producing the cerium-based abrasive with good productivity, the particle size (D 50 ) is preferably 0.10 μm or more, more preferably 0.3 μm or more, further preferably 0.5 μm or more, and further preferably 0.7 μm or more. From the viewpoint of being able to reduce polishing scratches and smooth the polished surface well to obtain excellent polishing performance, D 50 It is preferably 10.0 μm or less, more preferably 5.0 μm or less, and further preferably 3.0 μm or less.

[0052] From the viewpoint of suppressing the occurrence of scratches (scars) on the polished surface, the specific surface area of ​​the cerium-based abrasive of the present embodiment is preferably 1.0 m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, preferably 10.0 m / g from the viewpoint of increasing the polishing rate 2 / g or less, more preferably 8.0m 2 / g or less, more preferably 7.0m 2 / g or less, and more preferably 6.0m 2 / g or less.

[0053] In this specification, the specific surface area is a value measured by the BET method (single point method).

[0054] From the viewpoint of improving the polishing rate, the cerium-based abrasive of the present embodiment may contain fluorine atoms.

[0055] When the cerium-based abrasive contains fluorine atoms, the fluorine atom content in the cerium-based abrasive is preferably 0.1 mass % or more, more preferably 1.0 mass % or more, and further preferably 3.0 mass % or more from the viewpoint of increasing the polishing rate, and is preferably 10.0 mass % or less, more preferably 9.0 mass % or less, further preferably 8.0 mass % or less, and further preferably 7.0 mass % or less from the viewpoint of suppressing the occurrence of scratches on the polished surface.

[0056] The fluorine atom content in the cerium-based abrasive can be measured by alkali-melting the cerium-based abrasive to form an aqueous solution and then using an ion electrode method.

[0057] From the viewpoint of increasing the polishing rate, the TREO in the cerium-based abrasive of the present embodiment is preferably 85.0 mass % or more, more preferably 90.0 mass % or more, and further preferably 92.0 mass % or more. From the viewpoint of containing elements other than the elements constituting TREO, further increasing the polishing rate, and suppressing the occurrence of surface defects (fine irregularities on the surface) of the polished surface, the TREO is preferably 99.0 mass % or less, more preferably 97.0 mass % or less, and further preferably 96.0 mass % or less.

[0058] (Mixed rare earth abrasive particles)

[0059] The "mixed" rare earth abrasive particles in this embodiment mean containing a plurality of rare earth elements. The mixed rare earth abrasive particles may contain rare earth elements other than Ce and La (lanthanum). Examples of the rare earth elements include Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, and Yb.

[0060] From the viewpoint of producing the cerium-based abrasive with good productivity, the particle size (D50 ) is preferably 0.10 μm or more, more preferably 0.3 μm or more, further preferably 0.5 μm or more, and further preferably 0.7 μm or more. From the viewpoint of reducing grinding scratches, smoothing the grinding surface and obtaining excellent grinding performance, it is preferably 10.0 μm or less, more preferably 5.0 μm or less, and further preferably 3.0 μm or less.

[0061] From the viewpoint of suppressing the occurrence of scratches (scars) on the polished surface, the specific surface area of ​​the mixed rare earth abrasive particles of this embodiment is preferably 1.0 m 2 / g or more, more preferably 2.0m 2 / g or more, more preferably 3.0m 2 / g or more, preferably 10.0 m / g from the viewpoint of increasing the polishing rate 2 / g or less, more preferably 8.0m 2 / g or less, more preferably 7.0m 2 / g or less, and more preferably 6.0m 2 / g or less.

[0062] In this specification, the specific surface area is a value measured by the BET method (single point method).

[0063] From the viewpoint of improving the polishing rate, the mixed rare earth abrasive particles of the present embodiment may contain fluorine atoms.

[0064] When the mixed rare earth abrasive material particles contain fluorine atoms, from the viewpoint of increasing the polishing speed, the fluorine atom content in the mixed rare earth abrasive material particles is preferably 0.1 mass % or more, more preferably 1.0 mass % or more, and further preferably 3.0 mass % or more. From the viewpoint of suppressing the occurrence of scratches on the polished surface, it is preferably 10.0 mass % or less, more preferably 9.0 mass % or less, further preferably 8.0 mass % or less, and further preferably 7.0 mass % or less.

[0065] (Lanthanum Dissolution Inhibitor)

[0066] The cerium-based abrasive of the present embodiment may contain a lanthanum dissolution inhibitor for suppressing the dissolution of lanthanum in addition to the mixed rare earth abrasive particles.

[0067] The lanthanum dissolution inhibitor is preferably a substance having a function of converting lanthanum ions dissolved in water, a water-soluble organic solvent, etc. into insoluble salts and precipitating them, or a substance having a function of immobilizing lanthanum ions by chelation.

[0068] As such a lanthanum dissolution inhibitor, preferably, at least one substance selected from alkali metal carbonates, alkali metal phosphates, alkali metal hydroxides, alkali metal sulfates, alkali metal nitrates, alkali metal organic acid salts, alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal hydroxides, alkaline earth metal sulfates, alkaline earth metal nitrates, alkaline earth metal organic acid salts, ammonium carbonates, ammonium phosphates, ammonium hydroxides, ammonium sulfates, ammonium nitrates and ammonium organic acid salts are selected. From the viewpoint of the safety of the generated salt, more preferably, at least one substance selected from alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal organic acid salts and alkali metal carbonates are selected.

[0069] As the alkali metal, sodium and potassium are preferred from the viewpoint of safety of the resulting salt, and sodium is more preferred.

[0070] From the same viewpoint, calcium and magnesium are preferred as the alkaline earth metal.

[0071] Specifically, preferred lanthanum dissolution inhibitors include monocalcium phosphate, calcium hydrogen phosphate, calcium hydroxide, calcium carbonate, calcium gluconate, calcium citrate, sodium bicarbonate, ammonium bicarbonate, magnesium hydrogen phosphate, and calcium hydrogen phosphate. Among them, calcium hydrogen phosphate is more preferred from the viewpoints of suppressing the occurrence of skin roughness and dermatitis, the safety of the generated salt, and suppressing the occurrence of scratches on the polished surface.

[0072] The lanthanum dissolution inhibitor may be used alone or in combination of two or more.

[0073] In addition, from the viewpoint of further suppressing the occurrence of rough skin and dermatitis, the molecular weight of the lanthanum dissolution inhibitor is preferably 50 or more, more preferably 75 or more, further preferably 100 or more, preferably 300 or less, more preferably 200 or less, further preferably 150 or less. When the molecular weight is 300 or less, the reactivity with lanthanum ions is high, and the lanthanum dissolution inhibitory effect is high, so it is preferred.

[0074] In the case where the cerium-based abrasive of this embodiment contains a lanthanum dissolution inhibitor, the cerium-based abrasive can be a single-dose type that pre-contains the lanthanum dissolution inhibitor, or a two-dose type that contains a first dose and a second dose, wherein the first dose contains the above-mentioned mixed rare earth abrasive particles and the second dose contains the lanthanum dissolution inhibitor.

[0075] In the case where the cerium-based abrasive is a two-part formulation comprising a first part containing the mixed rare earth abrasive particles and a second part containing a lanthanum dissolution inhibitor, etc., from the viewpoint of increasing the polishing rate, the content of the mixed rare earth abrasive particles in the first part is preferably 85.0 mass % or more, more preferably 90.0 mass % or more, and further preferably 92.0 mass % or more, and from the viewpoint of suppressing the occurrence of skin roughness and dermatitis, it is preferably 99.9 mass % or less, more preferably 99.5 mass % or less, and further preferably 99.2 mass % or less.

[0076] The content of the lanthanum dissolution inhibitor in the cerium-based abrasive is preferably 0.95 parts by mass or less, more preferably 0.85 parts by mass or less, and further preferably 0.75 parts by mass or less, based on cost, in both the single-dose form and the double-dose form, relative to 100 parts by mass of the mixed rare earth abrasive particles. In addition, from the viewpoint of inhibiting the occurrence of rough skin and dermatitis, it is preferably 0.001 parts by mass or more, more preferably 0.01 parts by mass or more, and further preferably 0.1 parts by mass or more.

[0077] In addition, the content of the lanthanum dissolution inhibitor in the cerium-based abrasive is preferably 0.95% by mass or less, more preferably 0.90% by mass or less, further preferably 0.80% by mass or less, and further preferably 0.70% by mass or less from the viewpoint of cost in both the single-dose type and the double-dose type. In addition, from the viewpoint of suppressing the occurrence of rough skin and dermatitis, it is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, further preferably 0.05% by mass or more, and further preferably 0.1% by mass or more.

[0078] (additive)

[0079] In order to improve dispersibility, prevent sedimentation, prevent solidification, improve stability and improve workability, the cerium system abrasive material of the present embodiment can also be used as additives to add water-soluble polymer substances such as polymer dispersants such as glycols such as ethylene glycol, polyethylene glycol, sodium salts of polyacrylic acid, polycarboxylic acid polymers, polysulfonic acid polymers, cellulose ethers such as methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, phosphoric acid compounds, etc. They can be used alone or in combination with more than two kinds. When adding additives, among these materials, from the viewpoint of further improving dispersibility, preventing sedimentation, preventing solidification, improving stability and improving workability, preferred polymer dispersants, phosphoric acid compounds and cellulose ethers.

[0080] Examples of the polymer dispersant include poly(meth)acrylic acid, polyhydroxy(meth)acrylic acid, (meth)acrylic acid copolymers such as copolymers of (meth)acrylic acid and maleic acid, copolymers of olefins and maleic acid, copolymers of maleic acid and alkylene oxide adducts such as ethylene oxide and propylene oxide of allyl alcohol, copolymers of allylsulfonic acid and maleic acid, or alkali metal salts thereof such as sodium salts and potassium salts. Among them, polyacrylic acid, copolymers of acrylic acid and maleic acid, or alkali metal salts thereof are preferred, copolymers of acrylic acid and maleic acid or alkali metal salts thereof are more preferred, and sodium salts of copolymers of acrylic acid and maleic acid are further preferred.

[0081] Examples of the phosphoric acid compound include inorganic phosphoric acids such as tripolyphosphoric acid, pyrophosphoric acid, tetrametaphosphoric acid, hexametaphosphoric acid, orthophosphoric acid, and phosphorous acid; organic phosphonic acids such as aminotrimethylenephosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, ethylenediaminetetramethylenephosphonic acid, and diethylenetriaminepentamethylenephosphonic acid; or alkali metal salts thereof such as sodium salts and potassium salts. Among them, tripolyphosphoric acid, pyrophosphoric acid, hexametaphosphoric acid, or alkali metal salts thereof are preferred, and sodium tripolyphosphate is more preferred.

[0082] When the cerium-based abrasive contains an additive, from the viewpoint of improving dispersibility, preventing sedimentation, preventing solidification, improving stability and improving workability, the content of the additive is preferably 0.01 parts by mass or more, more preferably 0.1 parts by mass or more, further preferably 0.3 parts by mass or more, and further preferably 0.5 parts by mass or more, relative to 100 parts by mass of the mixed rare earth abrasive particles. From the viewpoint of cost, it is preferably 10.0 parts by mass or less, more preferably 5.0 parts by mass or less, and further preferably 3.0 parts by mass or less.

[0083] In addition, when the cerium-based abrasive contains an additive, the content of the additive in the cerium-based abrasive is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, further preferably 0.3% by mass or more, and further preferably 0.5% by mass or more, from the viewpoint of improving dispersibility, preventing sedimentation, preventing solidification, improving stability, and improving workability, and is preferably 10.0% by mass or less, more preferably 5.0% by mass or less, and further preferably 3.0% by mass or less from the viewpoint of cost.

[0084] [Method for producing cerium-based abrasive]

[0085] The method for producing the cerium-based abrasive is not particularly limited, but specifically, the cerium-based abrasive is preferably produced through the following steps: a step (1) of preparing a mixed light rare earth compound; a step (2) of producing a mixed rare earth oxide raw material from the mixed light rare earth compound; and a step (3) of wet-grinding the mixed rare earth oxide raw material, calcining, crushing and classifying to obtain mixed rare earth abrasive particles. In addition, from the viewpoint of further suppressing the occurrence of rough skin and dermatitis, it is more preferable to produce the cerium-based abrasive through a step (4) after the above-mentioned step (3), in which a mixed lanthanum dissolution inhibitor is added, or a second agent containing a lanthanum dissolution inhibitor is prepared. The "mixing" mentioned here is also synonymous with the "mixing" of the above-mentioned mixed rare earth abrasive particles.

[0086] Hereinafter, each step will be described in order.

[0087] (Process (1))

[0088] In step (1), a mixed light rare earth compound is prepared.

[0089] The preparation method of the mixed light rare earth compound is not particularly limited. The mixed light rare earth compound is obtained, for example, by reducing the impurity components other than rare earth elements and medium and heavy rare earths from the ore containing rare earth elements by chemical treatment. As the mixed light rare earth compound, a mixed light rare earth compound in which the impurity components of non-rare earth components such as alkali metals, alkaline earth metals and radioactive substances and the content of medium and heavy rare earths are reduced is preferred.

[0090] In this specification, medium and heavy rare earth elements refer to rare earth elements having an atomic number larger than that of Pm, and rare earth elements other than medium and heavy rare earth elements are referred to as light rare earth elements.

[0091] As the ore containing a rare earth element, for example, a rare earth concentrate obtained from a raw material ore such as natural bastnasite or pyrocatecholite containing a large amount of Ce can be preferably used.

[0092] In the preparation of mixed light rare earth compounds, sulfuric acid roasting is a common method as a chemical treatment method for reducing the content of impurities. Sulfuric acid roasting is a method in which the crushed raw ore is roasted with sulfuric acid to generate sulfate (rare earth sulfate), the sulfate is dissolved in water to form a rare earth sulfate solution, and the impurities as insolubles are removed by filtration. The content of impurities in the mixed light rare earth compound is preferably reduced to 1.0 mass % or less.

[0093] In addition, as a chemical treatment method for reducing the content of medium and heavy rare earths, for example, the following can be performed: carbonate is added to the rare earth sulfate solution after the sulfuric acid roasting to prepare crude rare earth carbonate, hydrochloric acid is added thereto to prepare a mixed rare earth chloride aqueous solution, and solvent extraction is performed using an organic solvent. In the solvent extraction, the respective contents of cerium, lanthanum and other light rare earths can be adjusted as needed by using known methods such as adjustment of the degree of extraction and use of additives. The content of medium and heavy rare earths in the mixed light rare earth compound is preferably reduced to less than 1.0 mass%.

[0094] (Process (2))

[0095] In step (2), a mixed rare earth oxide raw material is produced from a mixed light rare earth compound.

[0096] The method for producing a mixed rare earth oxide raw material from a mixed light rare earth compound is not particularly limited. The mixed rare earth oxide raw material is obtained by, for example, producing a mixed rare earth carbonate as a carbonate using a mixed light rare earth compound and sodium carbonate, ammonium bicarbonate, etc., and calcining the mixed rare earth carbonate.

[0097] The calcination temperature when the mixed rare earth carbonate is calcined to obtain the mixed rare earth oxide raw material is appropriately adjusted according to the composition of the mixed rare earth carbonate, but is preferably 500 to 1200° C., more preferably 600 to 1100° C., and further preferably 700 to 1000° C. The calcination time is preferably 0.5 to 48 hours, more preferably 1 to 40 hours, and further preferably 1.5 to 30 hours. The calcination atmosphere is preferably an air atmosphere.

[0098] The mixed rare earth oxide raw material may be mechanically crushed after calcination to adjust the particles to a desired particle size.

[0099] Furthermore, mixed rare earth oxide raw materials are also commercially available, and commercially available products may also be used. Mixed rare earth oxide raw materials can be obtained by, for example, calcining mixed light rare earth compounds such as mixed rare earth carbonates, mixed rare earth monocarbonates, mixed rare earth oxalates, and mixed rare earth hydroxides, so mixed rare earth carbonates, mixed rare earth monocarbonates, mixed rare earth oxalates, and the like, which are the raw materials for their production, may sometimes remain in commercially available mixed rare earth oxide raw materials.

[0100] (Process (3))

[0101] In step (3), the mixed rare earth oxide raw material is wet-pulverized, calcined, crushed and classified to obtain mixed rare earth abrasive particles.

[0102] Wet pulverization is preferably performed using a medium mill such as a wet ball mill from the viewpoint of obtaining uniform mixed rare earth grinding material particles. As the dispersion medium, water, a water-soluble organic solvent, or the like is preferably used.

[0103] After wet pulverization, the mixed rare earth abrasive particles are obtained by drying, calcining, crushing and classification.

[0104] Drying, calcining, crushing and classification can be performed in the same manner as the methods used in the conventional production of mixed rare earth abrasive particles.

[0105] In addition, from the viewpoint of sufficiently reacting the raw material to be fired by firing, the firing temperature is preferably 600 to 1200° C., more preferably 650 to 1150° C., and even more preferably 700 to 1100° C. The firing time at the target set temperature is preferably 0.1 to 10 hours, more preferably 0.5 to 6 hours, and even more preferably 0.5 to 4 hours. The firing atmosphere is preferably air.

[0106] From the viewpoint of increasing the polishing speed, the mixed rare earth abrasive particles are sometimes made to contain fluorine atoms. In this case, the method for making it contain fluorine atoms is not particularly limited, but preferably a method of mixing a mixed rare earth oxide raw material with a mixed rare earth fluoride raw material, wet-grinding, and then calcining, crushing and classifying to obtain the mixed rare earth abrasive particles.

[0107] The method for obtaining the mixed fluoride rare earth raw material is not particularly limited. For example, it can be obtained by adding a fluoride such as hydrofluoric acid, ammonium fluoride or acidic ammonium fluoride as a fluorine source to the above-mentioned mixed light rare earth compound and performing heat treatment. The above-mentioned heat treatment is preferably 400° C. or less from the viewpoint of obtaining a cerium-based abrasive material having a homogeneous and excellent grinding property. Furthermore, the heat treatment atmosphere is preferably air. The heat treatment time is preferably 0.1 to 10 hours, more preferably 0.5 to 5 hours, and further preferably 1.0 to 4 hours. The calcination atmosphere is preferably an air atmosphere.

[0108] The method of mixing a mixed rare earth fluoride raw material with a mixed rare earth oxide raw material to obtain mixed rare earth abrasive material particles is safe and low-cost compared to the method of directly adding fluorides such as ammonium fluoride and hydrofluoric acid to a mixed rare earth oxide raw material to obtain mixed rare earth abrasive material particles, and can easily obtain mixed rare earth abrasive material particles containing fluorine.

[0109] The TREO in the mixed fluorinated rare earth raw material is preferably 75% by mass or more, more preferably 80% by mass or more, and further preferably 82% by mass or more. In addition, the mixed fluorinated rare earth raw material is preferably composed of cerium as the main component among all the rare earth elements contained. The oxide-converted content of cerium in TREO (CeO2 amount / TREO) is preferably 55.0% by mass or more, and from the viewpoint of improving the grinding speed, it is more preferably 60.0% by mass or more, more preferably 62.0% by mass or more, and further preferably 64.0% by mass or more. In addition, from the viewpoint of ensuring the content of rare earth elements other than Ce and suppressing the occurrence of surface defects on the grinding surface, the CeO2 amount / TREO is preferably 90.0% by mass or less, more preferably 80.0% by mass or less, further preferably 75.0% by mass or less, and further preferably 70.0% by mass or less.

[0110] The fluorine atom content in the mixed rare earth fluoride raw material is preferably 10 to 30% by mass, more preferably 15 to 30% by mass, and even more preferably 20 to 30% by mass.

[0111] The amount of the mixed rare earth fluoride raw material added to the mixed rare earth oxide raw material is appropriately determined according to the fluorine atom content required for the manufactured cerium-based abrasive material. From the viewpoint of obtaining excellent grinding properties, the amount of the mixed rare earth fluoride raw material is preferably added in a manner of 1 to 40 mass %, more preferably 3 to 35 mass %, and further preferably 5 to 30 mass %, relative to the total of 100 mass % of the mixed rare earth oxide raw material and the mixed rare earth fluoride raw material.

[0112] (Process (4))

[0113] Step (4) is to add a mixed lanthanum dissolution inhibitor to the mixed rare earth abrasive particles obtained in step (3) after step (3), or to prepare a second agent containing the lanthanum dissolution inhibitor.

[0114] In this embodiment, when the cerium-based abrasive is a single-dose type, the mixed rare earth abrasive particles can be used as the cerium-based abrasive without going through step (4), or a mixed lanthanum dissolution inhibitor can be added to the mixed rare earth abrasive particles obtained in step (3) to form the cerium-based abrasive. In addition, a mixed additive can be added together with the lanthanum dissolution inhibitor as needed.

[0115] The mixing method is not particularly limited, and for example, mixing may be performed using a mixer such as a batch mixer, or using a media mill such as a ball mill or a bead mill.

[0116] In the present embodiment, when the cerium-based abrasive is a two-part type, the second part containing the lanthanum dissolution inhibitor is prepared by step (4).

[0117] In this embodiment, when the cerium-based abrasive material is a two-part formulation comprising a first part containing the above-mentioned mixed rare earth abrasive material particles and a second part containing a lanthanum dissolution inhibitor, it can be prepared separately as a first part containing the above-mentioned mixed rare earth abrasive material particles and a second part containing a lanthanum dissolution inhibitor, and the first part and the second part are mixed when manufacturing the polishing liquid.

[0118] The second agent may contain water, a water-soluble organic solvent, an additive, etc. in addition to the lanthanum dissolution inhibitor, or may not contain them.

[0119] [Grinding fluid]

[0120] The polishing liquid of the present embodiment contains the cerium-based abrasive material as described above and one or more substances selected from water and a water-soluble organic solvent. From the viewpoint of further suppressing the occurrence of rough skin and dermatitis, the above-mentioned polishing liquid preferably contains a lanthanum dissolution inhibitor. In addition, the above-mentioned polishing liquid may also contain components other than the cerium-based abrasive material, one or more substances selected from water and a water-soluble organic solvent, and the lanthanum dissolution inhibitor.

[0121] The polishing liquid of this embodiment is a polishing liquid that suppresses skin roughness, dermatitis, and the like that occur due to adhesion to human skin.

[0122] The above-mentioned polishing liquid is preferably used in a range of 0.1 to 40.0 mass % in terms of exerting good polishing performance and cost, more preferably 1.0 to 35.0 mass %, further preferably 3.0 to 30.0 mass %, and further preferably 5.0 to 20.0 mass %.

[0123] Furthermore, the above-mentioned polishing liquid can also be a polishing liquid to which additives such as pH adjusters, defoaming agents, rust inhibitors, etc. are added as needed within a range that does not hinder the polishing performance when preparing the polishing liquid, taking into account the polishing object, the specifications of the polishing equipment, etc.

[0124] The above-mentioned polishing liquid can be particularly suitably used for fine grinding (polishing) of various glass materials and glass products such as glass substrates for optical disks and magnetic disks, glass substrates for liquid crystal displays, glass substrates for color filters and photomasks, and glass substrates for optical lenses.

[0125] [Method for producing polishing liquid]

[0126] The method for producing a polishing liquid of the present invention is a method for producing a polishing liquid containing the above-mentioned cerium-based abrasive and one or more substances selected from water and a water-soluble organic solvent.

[0127] In one embodiment of the present invention, the method for producing a polishing liquid comprises: a step (I) of mixing the cerium-based abrasive with one or more substances selected from the water and the water-soluble organic solvent to form a slurry. In this case, the cerium-based abrasive may contain the lanthanum dissolution inhibitor or may not contain the lanthanum dissolution inhibitor.

[0128] When the cerium-based abrasive is a two-part type comprising a first part containing mixed rare earth abrasive particles and a second part containing a lanthanum dissolution inhibitor, step (I) is performed using the first part and the second part as the cerium-based abrasive.

[0129] In step (I), the method of slurrying is not particularly limited, and for example, slurrying can be performed by mixing with a stirrer, or by using a pulverizer such as a wet ball mill, an attritor mill, or a bead mill.

[0130] In another embodiment of the present invention, the method for producing a polishing liquid comprises: a step (II) of mixing the cerium-based abrasive, the lanthanum dissolution inhibitor, and one or more substances selected from the water and the water-soluble organic solvent to form a slurry. In this case, the cerium-based abrasive may contain the lanthanum dissolution inhibitor or may not contain the lanthanum dissolution inhibitor.

[0131] The method of forming the slurry in the step (II) is the same as the method of forming the slurry in the above-mentioned step (I).

[0132] In another embodiment of the present invention, the method for producing a polishing liquid comprises: a step (III) of mixing the cerium-based abrasive material and one or more substances selected from the water and the water-soluble organic solvent to form a slurry; and a step (IV) of adding and mixing the lanthanum dissolution inhibitor to the slurry obtained in the step (III). The cerium-based abrasive material may contain the lanthanum dissolution inhibitor or may not contain the lanthanum dissolution inhibitor.

[0133] The method of slurrying in the step (III) is the same as the method of slurrying in the above-mentioned step (I).

[0134] [Glass grinding method]

[0135] The glass polishing method of the present invention is a method of polishing using the polishing liquid as described above.

[0136] The above-mentioned glass polishing method is not particularly limited except for using the above-mentioned polishing liquid, and a method using a known polishing device etc. can be applied. The above-mentioned polishing liquid can be used by a known method when fine polishing such as mirror polishing of glass materials using a single-sided grinder or a double-sided grinder.

[0137] Example

[0138] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to the following examples.

[0139] Furthermore, the preparation of the mixed rare earth oxide raw material, the preparation of the mixed rare earth fluoride raw material, the oxide conversion content of each rare earth element in TREO and TREO in the examples and comparative examples (CeO2 amount / TREO, La2O3 amount / TREO, Nd2O3 amount / TREO, Pr6O 11 The content of fluorine atom (T / TREO) and fluorine atom content are calculated as follows.

[0140] 〔TREO〕

[0141] Ammonia water is added to the solution obtained by acid dissolving the test sample. The resulting precipitate is filtered and washed to remove the alkali metal, and then acid dissolution is performed again. Oxalic acid is added to the solution, and the resulting precipitate is calcined at 800°C in the air for 2 hours, and TREO is calculated by the weight method. In addition, the TREO of the mixed rare earth abrasive particles is obtained by "the total rare earth oxide mass obtained after calcination / the mass of the mixed rare earth abrasive particles before the acid dissolution treatment", and the TREO of the cerium-based abrasive is obtained by "the total rare earth oxide mass obtained after calcination / the mass of the cerium-based abrasive before the acid dissolution treatment".

[0142] [Content of each rare earth element in TREO as oxide]

[0143] The amount of each rare earth element is measured by dissolving the measurement sample with acid using the ICP-AES method, and the value of the value obtained by converting the amount of each rare earth element as an oxide relative to TREO is calculated to obtain the value.

[0144] 〔Fluorine atom content〕

[0145] The measurement sample was alkali-melted and extracted with warm water, and then measured using a fluoride ion meter (manufactured by Horiba, Ltd.; ion electrode method).

[0146] [Preparation of mixed rare earth oxide raw materials]

[0147] (Mixed rare earth oxide raw material A)

[0148] A raw material ore (rare earth concentrate) containing 47% by mass of TREO, 2% by mass of medium and heavy rare earths in terms of oxide conversion, and 8% by mass of neodymium in terms of oxide conversion was treated by a sulfuric acid roasting method and a solvent extraction method to reduce impurity components other than rare earth elements to less than 1% by mass, and to reduce medium and heavy rare earths to less than 1% by mass in terms of oxide conversion, thereby obtaining a mixed light rare earth compound in which the contents of rare earth elements were adjusted. In the mixed light rare earth compound, the content of cerium in terms of oxide conversion ([CeO2]) (CeO2 amount / TREO) in TREO was 64.7% by mass, the content of lanthanum in terms of oxide conversion ([La2O3]) (La2O3 amount / TREO) was 34.1% by mass, the content of neodymium in terms of oxide conversion ([Nd2O3]) (Nd2O3 amount / TREO) was 0.6% by mass, and the content of praseodymium in terms of oxide conversion ([Pr6O 11 ]) content (Pr6O 11 The amount / TREO) is 0.2 mass %.

[0149] The mixed light rare earth compound was treated with ammonium bicarbonate to obtain mixed rare earth carbonate. The TREO content of the mixed rare earth carbonate was 49% by mass.

[0150] The mixed rare earth carbonate was heat treated in a calcining furnace in the atmosphere at 800°C for 10 hours to obtain a mixed rare earth oxide raw material A. TREO, CeO2 amount / TREO, La2O3 amount / TREO, Nd2O3 amount / TREO, and Pr6O 11 The amounts / TREO are shown in Table 1.

[0151] (Mixed rare earth oxide raw materials B to E)

[0152] In the same manner as the preparation of the mixed rare earth oxide raw material A, mixed light rare earth compounds were used and the treatment conditions and the heat treatment conditions of the mixed rare earth carbonate were adjusted to prepare mixed rare earth oxide raw materials B to E. The TREO, CeO2 amount / TREO, La2O3 amount / TREO, Nd2O3 amount / TREO, and Pr6O 11 The amounts / TREO are shown in Table 1.

[0153] Table 1

[0154]

[0155] *1: Indicates the content of cerium oxide (CeO2) in TREO.

[0156] *2: Indicates the content of lanthanum oxide (La2O3) in TREO.

[0157] *3: Indicates the content of neodymium oxide (Nd2O3) in TREO.

[0158] *4: Indicates the oxide of praseodymium (Pr6O 11 )Converted content.

[0159] [Preparation of mixed rare earth fluoride raw materials]

[0160] (Mixed rare earth fluoride raw material F)

[0161] After adding hydrofluoric acid to the mixed light rare earth compound and mixing, heat treatment was performed in air at 400°C for 2 hours to obtain a mixed rare earth fluoride raw material F. The TREO, CeO2 amount / TREO, and fluorine content of the mixed rare earth fluoride raw material F are shown in Table 2.

[0162] (Mixed rare earth fluoride raw materials G~I)

[0163] Mixed rare earth fluoride raw materials G to I were prepared by using mixed light rare earth compounds and adjusting the treatment conditions in the same manner as in the preparation of mixed rare earth fluoride raw material F. TREO, CeO2 amount / TREO, and fluorine content of mixed rare earth fluoride raw materials G to I are shown in Table 2.

[0164] Table 2

[0165]

[0166] *1: Indicates the content of cerium oxide (CeO2) in TREO.

[0167] [Manufacture of cerium-based abrasives]

[0168] According to the following examples and comparative examples, cerium-based abrasives were produced.

[0169] The details of the additives used in the following Examples and Comparative Examples are shown below.

[0170] Additive 1: Sodium tripolyphosphate (Kanto Chemical Co., Ltd.): molecular weight over 300

[0171] Additive 2: Sodium salt of polyacrylic acid "Poiz 530" (Kao Corporation): molecular weight over 300

[0172] Additive 3: Sodium salt of copolymer of acrylic acid and maleic acid "Poiz 521" (Kao Corporation): molecular weight over 300

[0173] Additive 4: Carboxymethyl cellulose (Kanto Chemical Co., Ltd.): molecular weight over 300

[0174] Additive 5: Crystalline cellulose "Cellulose Crystals" (Kanto Chemical Co., Ltd.): molecular weight over 300

[0175] (Example 1)

[0176] 1000 kg of water and 1400 kg of the mixed rare earth oxide raw material A and the mixed rare earth fluoride raw material F (mass ratio of 76:24) were stirred and mixed in a slurry tank, and then mixed and pulverized for 17 hours using a wet ball mill (media: zirconia balls with a diameter of 5 mm) to obtain a uniform mixed solution.

[0177] The mixed solution was placed in a rotary kiln, dried at 700°C for 1 hour in the air, and then calcined at 960°C for 4 hours. The calcined body was naturally cooled, crushed, and classified to obtain mixed rare earth abrasive particles. 0.1 parts by mass of calcium hydrogen phosphate as a lanthanum dissolution inhibitor was added to the mixed rare earth abrasive particles relative to 100 parts by mass of the mixed rare earth abrasive particles, and mixed using a stirrer to produce a cerium-based abrasive.

[0178] (Examples 2 to 25 and Comparative Examples 1 to 5)

[0179] A cerium-based abrasive was produced in the same manner as in Example 1 except that the mixed rare earth oxide raw material, the mixed rare earth fluoride raw material, the calcination temperature, the lanthanum dissolution inhibitor, and the additives 1 to 5 were as shown in Tables 3 and 4.

[0180] [Measurement of physical properties of mixed rare earth abrasive particles and cerium-based abrasives]

[0181] The mixed rare earth abrasive and the cerium-based abrasive produced as described above were subjected to the following physical property measurements. The results of the physical property measurements are shown in Tables 3 and 4 below.

[0182] (Particle size distribution D 50 )

[0183] The cerium-based abrasive or mixed rare earth abrasive particles were dispersed in pure water containing a dispersant to prepare a measurement sample. The particle size distribution of the cerium-based abrasive was measured using a Microtrac particle size distribution meter "MT3300 II" (manufactured by Nikkiso Co., Ltd.) by laser diffraction scattering method to determine the particle size distribution of the cerium-based abrasive. The particle size corresponding to 50% cumulative volume (D 50 ).

[0184] (Specific surface area)

[0185] The specific surface area of ​​the cerium-based abrasive or mixed rare earth abrasive particles was measured in accordance with "6.2 Flow method (3.5) Single point method" of JIS R 1626:1996 (Measurement method of specific surface area of ​​fine ceramic powder by gas adsorption BET method). Nitrogen gas was used as the adsorbent gas.

[0186] [Evaluation of Cerium-based Abrasives]

[0187] The cerium-based abrasives produced in the above-described Examples and Comparative Examples were evaluated as follows. The evaluation results are summarized in Table 5 below.

[0188] (Dissolved ion analysis)

[0189] The amounts of lanthanum, fluorine, and chlorine dissolved in water when the cerium-based abrasive was dispersed in water were calculated by ICP analysis and IC analysis.

[0190] [Preparation of samples for ICP analysis and IC analysis]

[0191] Into a 100 mL polyethylene container were placed 10 g of the cerium-based abrasive as a slurry component and 40 g of pure water, and 130 g of zirconia beads with a particle size of 1 mm as beads. The cerium-based abrasive was pulverized at a container speed of 210 rpm for 30 minutes using a ball mill stand to obtain a mixed solution.

[0192] 20 mL of the obtained mixed solution was taken and filtered with a membrane filter "SLHN033NS" (manufactured by Milipo Co., Ltd., Japan) with a mesh size of 0.45 μm, and then further filtered with a filter obtained by attaching a membrane filter "VSWP02500" (manufactured by Milipo Co., Ltd., Japan) with a mesh size of 0.025 μm to a syringe holder to prepare an analytical sample. In addition, ICP and IC analyses were performed using analytical samples within 48 hours after the analytical sample was prepared.

[0193] ICP analysis

[0194] After adding 10 mL of an aqueous solution obtained by mixing nitric acid (70% by mass) and ultrapure water at a volume ratio of 1:1 to 10 mL of the obtained analytical sample, the volume was fixed to 100 mL with ultrapure water to prepare an ICP analytical sample. The absorbance at a wavelength of 333.749 nm was measured for the ICP analytical sample using an ICP emission spectrometer "iCap7000Duo" (manufactured by Soundwave Science Co., Ltd.), and the mass concentration (mg / L) of lanthanum atoms was calculated.

[0195] IC Analysis

[0196] The obtained analysis sample 10 mL was diluted 20 times with ultrapure water to prepare an IC analysis sample. The IC analysis sample was measured using an ion chromatography system "ICS-1600" (manufactured by SAMOUR SIEFTIC CO., LTD.) with an eluent containing sodium carbonate and sodium bicarbonate to calculate the mass concentration (mg / L) of fluoride ions and chloride ions.

[0197] (Evaluation of skin roughness and dermatitis occurrence)

[0198] Into a 100 mL polyethylene container, 10 g of the cerium-based abrasive obtained in the embodiment and the comparative example and 40 g of pure water were added, and 130 g of zirconia beads with a particle size of 1 mm were added as beads. The cerium-based abrasive was pulverized for 30 minutes at a container speed of 210 rpm using a ball mill stand to obtain a mixed solution containing 20% ​​by mass of the cerium-based abrasive. The mixed solution was used to examine the occurrence of rough skin and dermatitis.

[0199] Specifically, for 5 subjects, 0.2 ml of the above-mentioned abrasive slurry as the test object was applied to the gauze part of the hemostatic patch, and after being fully stained, it was directly attached to the inner side of each person's forearm, and the state of the skin surface after 30 minutes was observed. If skin roughness or dermatitis occurs, itching and / or erythema will be observed. Based on this, if itching and erythema are not confirmed at all, it is considered to be no change, itching is considered to be slightly worse, erythema is slightly confirmed as worse, and erythema can be clearly confirmed as significantly worse, and the score is scored according to the following skin roughness evaluation criteria.

[0200] [Criteria for judging the effect of suppressing the occurrence of skin roughness and dermatitis]

[0201] 0 points: No change

[0202] 1 point: Slightly worse

[0203] 2 points: Deterioration

[0204] 3 points: Significant deterioration

[0205] (Grinding Evaluation)

[0206] Using the cerium-based abrasives obtained in the above-mentioned Examples and Comparative Examples, 48 ​​g of the cerium-based abrasives, 272 g of pure water, and a rotor were mixed. The mixture was placed in a 500 ml beaker and stirred at 500 rpm for 1 hour using a magnetic stirrer REXIM "RS-1DN" manufactured by Aswan Co., Ltd., to prepare an abrasive slurry containing 15% by mass of cerium-based abrasives. The abrasive slurry was used to grind a sample of alkali-free glass for TFT liquid crystal display (50 mm × 50 mm × 1.1 mm thick, 25 cm2 of grinding area) using a single-sided grinder under the following grinding conditions. 2 ) was ground and the grinding speed and grinding scratches were evaluated.

[0207] 〔Grinding conditions〕

[0208] Abrasive pad: Suede pad

[0209] Lower platform speed: 260rpm

[0210] Grinding pressure: 100g / cm 2

[0211] Grinding time: 20 minutes x 3 pieces

[0212] Each evaluation method is as follows.

[0213] 〔Grinding speed〕

[0214] The thickness of 5 locations of each sample before and after polishing was measured with a micrometer, and the average value of the thickness reduction (ΔT [μm]) was calculated. The average value of [ΔT / polishing time (20 minutes)] for the 3 samples was taken as the polishing rate.

[0215] 〔Grinding scar〕

[0216] The polished surface of the sample after polishing was observed at a magnification of 50 times using a differential interference microscope ("BX51M" manufactured by Olympus Corporation), the number of scratches was counted, and the average value for the three samples was determined.

[0217] Table 3

[0218]

[0219] *1: Indicates the content of cerium oxide (CeO2) in TREO.

[0220] *2: Indicates the content of lanthanum oxide (La2O3) in TREO.

[0221]

[0222] Table 5

[0223]

[0224] As can be seen from Table 5, the cerium-based abrasives (Examples 1 to 25) in which the lanthanum dissolution amount in the mixed solution obtained by the prescribed method was 40 mg / L or less were confirmed to be cerium-based abrasives that suppressed the occurrence of skin roughness and dermatitis. In addition, it was confirmed that the polishing liquid containing the above-mentioned cerium-based abrasives could suppress the occurrence of polishing scratches and perform polishing at a good polishing rate.

Claims

1. A cerium-based abrasive, comprising mixed rare earth abrasive particles, wherein the mixed rare earth abrasive particles contain lanthanum and cerium, The oxide-converted content of cerium in the total rare earth element oxide-converted content TREO is 55.0 mass % or more, 10 g of the cerium-based abrasive material and 40 g of pure water were placed in a 100 mL polyethylene container, and 130 g of zirconia beads with a particle size of 1 mm were added as beads. The cerium-based abrasive material was pulverized at a container speed of 210 rpm for 30 minutes using a ball mill stand, and the amount of lanthanum dissolved in the resulting mixed solution was less than 40 mg / L.

2. The cerium-based abrasive according to claim 1, further comprising a lanthanum dissolution inhibitor. 3 . The cerium-based abrasive according to claim 1 , which is a two-part type comprising a first part and a second part, wherein the first part contains the mixed rare earth abrasive particles and the second part contains a lanthanum dissolution inhibitor. 4 . The cerium-based abrasive according to claim 1 , comprising 0.1 to 10% by mass of fluorine atoms. 5 . The cerium-based abrasive according to claim 1 , wherein the lanthanum oxide-converted content in the TREO is 0.01 to 45.0% by mass.

6. The cerium-based abrasive according to claim 2 or 3, wherein the lanthanum dissolution inhibitor is one or more substances selected from alkali metal carbonates, alkali metal phosphates, alkali metal hydroxides, alkali metal sulfates, alkali metal nitrates, alkali metal organic acid salts, alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal hydroxides, alkaline earth metal sulfates, alkaline earth metal nitrates, alkaline earth metal organic acid salts, ammonium carbonates, ammonium phosphates, ammonium hydroxides, ammonium sulfates, ammonium nitrates and ammonium organic acid salts. 7 . The cerium-based abrasive according to claim 6 , wherein the lanthanum dissolution inhibitor is one or more substances selected from the group consisting of alkaline earth metal carbonates, alkaline earth metal phosphates, alkaline earth metal organic acid salts, and alkali metal carbonates. 8 . The cerium-based abrasive according to claim 2 , wherein the lanthanum dissolution inhibitor has a molecular weight of 300 or less. 9 . The cerium-based abrasive according to claim 2 , comprising 0.001 to 0.9 parts by mass of the lanthanum dissolution inhibitor based on 100 parts by mass of the mixed rare earth abrasive particles.

10. A polishing liquid comprising the cerium-based abrasive according to claim 1 and at least one substance selected from the group consisting of water and a water-soluble organic solvent.

11. A method for producing a polishing liquid, which is a method for producing the polishing liquid according to claim 10, comprising step I of mixing the cerium-based abrasive and one or more substances selected from the group consisting of water and the water-soluble organic solvent to form a slurry. 12 . The method for producing a polishing liquid according to claim 11 , wherein the cerium-based abrasive contains the lanthanum dissolution inhibitor.

13. A method for producing a polishing liquid, the method for producing the polishing liquid according to claim 10, comprising step II of mixing the cerium-based abrasive, the lanthanum dissolution inhibitor, and one or more substances selected from the group consisting of water and the water-soluble organic solvent to form a slurry.

14. A method for producing a polishing liquid, which is a method for producing the polishing liquid according to claim 10, comprising: Step III of mixing the cerium-based abrasive with one or more substances selected from the group consisting of water and the water-soluble organic solvent to form a slurry; and A step IV of adding and mixing the lanthanum dissolution inhibitor to the slurry obtained in the step III. 15 . The method for producing a polishing liquid according to claim 14 , wherein the cerium-based abrasive does not contain the lanthanum dissolution inhibitor.

16. A glass grinding method, comprising grinding using the grinding liquid according to claim 10.